2012
DOI: 10.3892/or.2012.1712
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor β1 in colorectal cancer: Correlation with clinicopathological variables

Abstract: Abstract. Colorectal cancer (CRC) is a common malignancy in both genders with a high death rate, accounting for about 56,000 each year in the USA only. In this study we examined the differences in CRC between the genders. We also looked for differences in the staining of the tumors and adjacent colonic mucosa to estrogen receptor β1 and its possible prognostic value. Fifty-five specimens from patients who underwent resection of colon cancer in our institute were sectioned and stained for estrogen receptor β1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Sex steroids, such as estrogen, are well-known for their role(s) in the control of cell differentiation and proliferation in estrogen-dependent tissues such as breast and endometrial tissues. However, it is noteworthy that estrogens appear to play a pivotal role in several types of human malignancies that are not considered as classical, estrogen-dependent, neoplasms, such as lung (6,7), urinary bladder (8) and gastrointestinal tract malignancies (9,10). Consequently, estrogenic pathways may be involved in the regulation of the biological behavior of ESCC.…”
Section: Introductionmentioning
confidence: 97%
“…Sex steroids, such as estrogen, are well-known for their role(s) in the control of cell differentiation and proliferation in estrogen-dependent tissues such as breast and endometrial tissues. However, it is noteworthy that estrogens appear to play a pivotal role in several types of human malignancies that are not considered as classical, estrogen-dependent, neoplasms, such as lung (6,7), urinary bladder (8) and gastrointestinal tract malignancies (9,10). Consequently, estrogenic pathways may be involved in the regulation of the biological behavior of ESCC.…”
Section: Introductionmentioning
confidence: 97%
“…reported that the expression of ER alpha was negative in all cases of colorectal cancer similar to the present study. 31 Studies from Waliszewski et al . uncovered that ER alpha was not expressed in the isolated colorectal cancer cells and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity was rated 0-3 (0, for no nuclear stain; 1, for the weakest nuclear stain; and 3, for the strongest nuclear stain) in comparison with the control stain. A score was calculated by multiplying the intensity of each field with the percentage of positively stained cells and then by a factor of 100 (i.e., if 20% of the nuclei in the slide was stained with an intensity of 2 the slide got a score of 40) (25). The mean score of five fields was named 'Topo II-α index' of the specimen.…”
Section: Expression Of Topoisomerase Ii-α Protein In Salivary Gland Tmentioning
confidence: 99%